2013
DOI: 10.3389/fnbot.2013.00001
|View full text |Cite
|
Sign up to set email alerts
|

A neurorobotic platform to test the influence of neuromodulatory signaling on anxious and curious behavior

Abstract: The vertebrate neuromodulatory systems are critical for appropriate value-laden responses to environmental challenges. Whereas changes in the overall level of dopamine (DA) have an effect on the organism's reward or curiosity-seeking behavior, changes in the level of serotonin (5-HT) can affect its level of anxiety or harm aversion. Moreover, top-down signals from frontal cortex can exert cognitive control on these neuromodulatory systems. The cholinergic (ACh) and noradrenergic (NE) systems affect the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 72 publications
(115 reference statements)
0
45
0
2
Order By: Relevance
“…In previous work, we have investigated the role of pleasure as reward in the maintenance of homeostasis in a reinforcement learning model (Cos et al, 2013). In this paper, we depart from the idea that pleasure is necessarily linked with reward—in the same way as value is not necessarily linked with reward (Krichmar & Röhrbein, 2013)—or with signaling biological usefulness, opening the door to the investigation of the role of other types of pleasure not directly related with the satisfaction of needs (Frijda, 2010), in addition to pleasure stemming from need satisfaction.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous work, we have investigated the role of pleasure as reward in the maintenance of homeostasis in a reinforcement learning model (Cos et al, 2013). In this paper, we depart from the idea that pleasure is necessarily linked with reward—in the same way as value is not necessarily linked with reward (Krichmar & Röhrbein, 2013)—or with signaling biological usefulness, opening the door to the investigation of the role of other types of pleasure not directly related with the satisfaction of needs (Frijda, 2010), in addition to pleasure stemming from need satisfaction.…”
Section: Introductionmentioning
confidence: 98%
“…In both cases, we have focused our study on the influence that pleasure has on the perception of external stimuli, and the underlying mechanism we have adopted to model pleasure is a simulation of hormonal modulation of perception. Unlike related work in robotics (Krichmar, 2008, 2012, 2013; Sporns & Alexander, 2002), our simulated hormone constitutes an abstract model aimed to capture the (gross) dynamics of modulation rather than modeling the behavior of specific chemicals underlying pleasure and more generally affective phenomena. Hormonal modulation has been used in robots for other purposes, such as behavior control (Moioli, Vargas, & Husbands, 2009), learning based on value and reward systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the reward error signal hypothesis, unexpected sensory stimuli that predict important biological reinforcers evoke phasic DA responses which reflect the expected amount of reward. Bolado-Gomez and Gurney (2013) suggest that the sensory prediction error signal is modulated by reward value. For example, the phasic firing evoked by response-contingent light- onset normally habituates, however this habituation is prevented if light-onset predicts a biologically important reinforcer.…”
Section: Discussionmentioning
confidence: 99%
“…Their model was inspired by cortical regions of the brain involved in unsupervised learning, as well as neuromodulatory systems responsible for providing intrinsic rewards through dopamine and regulating levels of attention through norepinephrine. Different neuromodulatory systems in the brain may be related to different aspects of value (Krichmar, 2013). In a model of multiple neuromodulatory systems, Krichmar showed that interactions between the dopaminergic (reward), serotoninergic (harm aversion), and the cholinergic/noradrenergic (novelty) systems could lead to interesting behavioral control in an autonomous robot.…”
mentioning
confidence: 99%